Entre expectativas e práticas: percepção dos Agentes de Gestão de Pessoas da UFPB em relação ao teletrabalho no âmbito de suas funções - Braga, Tânia Maria Correia (2025)
This study investigates the motivations and benefits of teleworking for Administrative Technicians in Education, particularly Human Resources Management Agents (AGPs), at the Federal University of Paraíba (UFPB), within the context of federal higher education institutions (IFES). With the increasing adoption of remote work driven by the COVID-19 pandemic, it became necessary to understand these employees' perceptions of this work modality and its impacts on their satisfaction, productivity, and well-being. The central questions of this research are: what are the motivations and benefits faced by UFPB AGPs when adopting teleworking, and how does this practice influence their job satisfaction? This question seeks to contribute to the understanding of how public policies and institutions can implement teleworking efficiently, promoting improvements in human resource management. The study uses a qualitative and quantitative approach, with a descriptive approach. The target population consisted of the AGPs (General Managers) affiliated with UFPB Campus I, totaling approximately 72 technicians, of whom 35 responded effectively to the questions. Data collection methods included questionnaires administered electronically via email, statistical analysis using Google Forms, and content analysis using Bardin's (2001) technique to understand the perceptions and experiences of these staff. The data indicate that telework, when well implemented, boosts productivity and improves the work environment. Its effectiveness depends on management strategies, efficient communication, and adequate infrastructure. The research concludes that telework represents a favorable configuration for UFPB's AGPs, provided it is supported by consistent institutional policies that consider the specificities of each employee and sector. Furthermore, it reinforces the need for continuous improvement of people management practices, including training and technological resources to ensure the success of this modality. Thus, the research provides support for the development of public policies and strategies for implementing telework in federal higher education institutions, contributing to the construction of a more efficient, sustainable environment focused on employee well-being.